Weight Status and Body Composition Dynamics in Children and Adolescents During the COVID-19 Pandemic - Azoulay, Erez; Yackobovitch-Gavan, Michal; Yaacov, Hadar; Gilboa, Inbar; Lopez, Adar; Sheppes, Tamar; Waksman, Yarden; Lebenthal, Yael; Brener, Avivit (Frontiers in Pediatrics, 2021)
Introduction: The preventive measures taken in attempt to prevent COVID-19 spread lead to closure of schools and leisure time activities. The impact of the pandemic on pediatric weight status is unclear, reports from around the world predict grave consequences with increasing obesity. We aimed to examine the change in body composition parameters of children and adolescents during the pandemic. Materials and methods: An observational study of 220 pediatric subjects (109 boys; mean current age 11.8±3.3 years; 37 with underweight, 123 with normal weight, and 60 with overweight/obesity) who underwent height and body composition measurements by bioelectrical impedance analysis, Tanita MC-780MA, GMON Professional Software) before and during the pandemic. Height, body mass index (BMI) and muscle-to-fat ratio (MFR) z-scores were calculated. Data collected from the participants’ medical files included home address for socioeconomic position calculation, pubertal stage, and self-reported sleep duration and physical activity performance. Results: The vast majority of the cohort (81.8%) had stable or improved MFR z-scores during the pandemic. MFR z-scores significantly increased in subjects with underweight (p=0.05) and normal weight (p=0.008), but not in subjects with overweight/obesity (p=0.169). There were significant associations in BMI z-scores (r=0.961, p<0.001) and MFR z-scores (r=0.854, p < 0.001) before and during the pandemic. A multivariate linear regression model identified socioeconomic position, pre-pandemic BMI z-scores, pre-pandemic MFR z-scores, and physical activity levels during the pandemic as predictors for delta MFR z-scores (F=12.267, p<0.001). Age, sex, pre-pandemic physical activity, and the time that had elapsed between initiation of the first nationwide lockdown and the BIA assessment during the pandemic did not emerge as predictors for delta MFR z-score. Conclusions: Our encouraging findings demonstrate improvement in body composition parameters of subjects with underweight and normal weight and stability in subjects with overweight/obesity. Engagement in physical activity during the pandemic predicted improvement, while lower socioeconomic position predicted deterioration.